Exploring cutting-edge research trends in safety knowledge within military environments - Radzi, Elias M.; Abdullah, Khairul H.; Aziz, Fazli Shah A. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The military environment is characterised by high-risk operations and activities that require a comprehensive understanding of safety knowledge to ensure personnel’s well-being and effectiveness. Indirectly, this scenario illustrates the military’s need to prioritise adequate safety and health management within their environment, just like other organisations. The current scientometric review aims to analyse research trends related to safety knowledge within military environments. Methods: This review utilised ScientoPy and VOSviewer to comprehend the nature of collected datasets from Scopus and Web of Science (WoS) databases. Results: The scholarly publication “Proceedings - IEEE Military Communications Conference MILCOM” is renowned for its extensive coverage of safety knowledge research for military environments. The keyword “emergency preparedness” has significantly impacted the thematic content of scholarly safety knowledge for the past three decades, from 1990 to 2023, as previous researchers used it most frequently. Based on overlay visualisation mapping, the current review demonstrates that the terms “emergency,” “COVID-19,” and “risk management” have been accorded greater significance since 2020. Conclusion: This study provides a thorough and worldwide perspective on the crucial subjects of safety knowledge in military settings. It is aimed at potential readers and researchers interested in better understanding these concepts and conducting more rigorous research on military safety.